2008
DOI: 10.1186/1472-6920-8-20
|View full text |Cite
|
Sign up to set email alerts
|

Students' perceptions of learning environment in an Indian medical school

Abstract: Background: Learning environment in any medical school is found to be important in determining students' academic success. This study was undertaken to compare the perceptions of first year and clinical phase students regarding the learning environment at Melaka Manipal Medical College (MMMC) (Manipal Campus) and also to identify the gender wise differences in their perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
126
8
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(184 citation statements)
references
References 8 publications
(10 reference statements)
34
126
8
8
Order By: Relevance
“…36 Creating a more accessible support system may help in diminishing the number of students who fail courses and the attrition rate. Similar to many other cohorts of students, 16,31,39,40,44 the overall perception of the cohorts in this study was that teachers were too authoritarian. This may be a manifestation of the "older type" of senior teacher who teaches by experience rather than by direction and may indicate that some teachers are still using conventional methods.…”
Section: Specific Implicationsmentioning
confidence: 67%
See 2 more Smart Citations
“…36 Creating a more accessible support system may help in diminishing the number of students who fail courses and the attrition rate. Similar to many other cohorts of students, 16,31,39,40,44 the overall perception of the cohorts in this study was that teachers were too authoritarian. This may be a manifestation of the "older type" of senior teacher who teaches by experience rather than by direction and may indicate that some teachers are still using conventional methods.…”
Section: Specific Implicationsmentioning
confidence: 67%
“…15,16,29,38,40,44 However, with individual items, there were statistical differences between female and male students for three items. Women perceived the items "the enjoyment outweighs the stress of studying chiropractic" and "my accommodation is pleasant" with higher negativity than males.…”
Section: Specific Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total DREEM domain score was higher for first year students than students receiving clinical teaching (Abraham et al, 2008) according to a study done in an Indian school. In some of the areas surveyed by the DREEM inventory, the first year students might not have been too sure how to respond to the survey, although that might have simply meant that the first year students were not yet too stressed from their studies.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Abraham et al and Kiran and Gowdappa reported DREEM scores as 117/200 and 121.5/200, respectively, from other parts of India. [8,9] The DREEM scores have been calculated from medical schools globally. Roff et al calculated DREEM score among Nigerian and Nepali students and the score was 118/200 and 130/200, respectively.…”
Section: Discussionmentioning
confidence: 99%